B cells enable autoreactive T cells to avoid suppression - Matthew Funsten; Renee de Pooter; Vineeth Varanasi; Michael Burrows; Katharine Block; Andrey Kuznetsov; David Serreze; Haochu Huang; Alexander Chervonsky (Proceedings of the National Academy of Sciences, 2026)
Clinical trials and experimental observations have shown that B cells are essential for development of T cell–mediated organ-specific autoimmunity, although their exact contribution is not clear. As antigen presentation by B cells is focused on antigens cognate to their antigen receptors, we reasoned that B cells would facilitate activation of T effector cells (Teff) with the same antigen specificity but would poorly activate regulatory T cells (Treg) due to insufficient presence of antigen-specific Tregs among polyclonal/multispecific Tregs at the early stages of pathogenesis. At the same time, activation of Teff by autoantigens presented by dendritic cells (DC) would be sensitive to by-stander suppression by Tregs as DCs express a variety of antigenic peptides. We used Teff cells (KRN) and B cells (121) reactive to the same antigen – glucose-6-phosphate-isomerase (GPI) to show that KRN T cells activation was sensitive to polyclonal Tregs only when activated by DCs but not by B cells. However, as expected, GPI-specific Tregs were fully capable of suppressing Teff activation by B cells. Our findings shed light on the role of B cells in organ-specific autoimmunity and provide knowledge-based support for application of anti-B cell immunotherapies.